UK key performance indicators and quality assurance standards for colonoscopy. Issue 12 (16th August 2016) - Rees, Colin J; Thomas Gibson, Siwan; Rutter, Matt D; Baragwanath, Phil; Pullan, Rupert; Feeney, Mark; Haslam, Neil
Abstract : Colonoscopy should be delivered by endoscopists performing high quality procedures. The British Society of Gastroenterology, the UK Joint Advisory Group on GI Endoscopy, and the Association of Coloproctology of Great Britain and Ireland have developed quality assurance measures and key performance indicators for the delivery of colonoscopy within the UK. This document sets minimal standards for delivery of procedures along with aspirational targets that all endoscopists should aim for.